ANALISA PENGARUH MACAM MACAM FLUIDA DAN VARIASI KIPAS TERHADAP EFEKTIFITAS PENYERAPAN PANAS PADA MOTOR BENSIN 135CC - Sulistyono, Djoko; Nuansa Gusti, Aris (MEKANIKA: Jurnal Teknik Mesin, 2017)
Radiator cooling system is by using a liquid fluid as a heat exchanger. How to work theradiator with ducted heat released by the motor is then absorbed by the fluid in the radiatorcoolant. the fan on the radiator is typically only the size of the already terstandart. Little bigfan sizes affect the performance of the radiator. This research was conducted with the aim ofanalyzing the influence of a range of different kinds of fluid in the radiator and the fanagainst variations in the effectiveness of absorption of heat radiator. In the study conducted acomparative test of the effectiveness of heat-absorption fluid 100% variation between RCPower coolant, RC Megacools 100% and 50% coolant Power RC + 50% RC Megacools witheach variation of the fan, the fan is standard, large, single fan and double fan on everyvariation of the fluid. Based on the results of observation and data analysis in fluid 100% RCPower coolant obtained value effectiveness 0.512 on fan standard. On the variation of singlelarge fan of 0.528, and variations of the double fan of 0.539. Then it can be inferred that thelarger the fan is used, then the ride also value their effectiveness. This is because the largerthe fan to make the air more and more collisions so that accelerate the process of absorptionof the heat from the radiator. Whereas in fluid, variations on the variations of the double fanwith fluid 100% RC Megacools obtained the value of effectiveness of 0.477. On the fluid 50%+ 50% Megacools RC RC Power coolant fluid and in 0.502 100% RC Power coolant of0.539. Then it can be inferred that the fluid with 100% Power RC cooant is the best fluidvalues effectiveness due to fluid 100% RC has a higher boiling point than in other variationsof the fluid.